Academic stress and adaptation to university life: mediation of cognitive-emotional regulation and social support - Restrepo, Jorge Emiro; Bedoya Cardona, Erika Yohanna; Cuartas Montoya, Gina Paula; Cassaretto Bardales , Mónica de los Milagros; Vilela Alemán, Yuliana Patty (Anales de Psicología / Annals of Psychology, 2023)
University life involve personal, social, academic, and institutional challenges to which the students must adapt not only to achieve academic success but also to guarantee a good physical and mental health during the career. This period can be influenced by stressful situations that can affect at personal and academic level. The objective of the present study was to determine, through an analysis with structural equations, whether various cognitive-emotional regulation strategies and perceived social support, act as mediators of the effect of stress on adaptation to university life in 555 Colombian university students (437 women, 78.7%) with ages from 16 to 49 years (M = 22.83; SD = 4.774). The results show that the cognitive-emotional regulation strategies positive (Focus and Reappraisal), negative (Rumination, Self-blame and Blaming others) and social